26Al/10Be ratios reveal the source of river sediments in the Kimberley, NW Australia. Issue 2 (5th December 2019) - Cazes, Gaël; Fink, David; Codilean, Alexandru T.; Fülöp, Réka‐Hajnalka; Fujioka, Toshiyuki; Wilcken, Klaus M.
Abstract: We use cosmogenic 10 Be and 26 Al in both bedrock and fluvial sediments to investigate controls on erosion rates and sediment supply to river basins at the regional scale in the Kimberley, NW Australia. The area is characterised by lithologically controlled morphologies such as cuestas, isolated mesas and extensive plateaus made of slightly dipping, extensively jointed sandstones. All sampled bedrock surfaces at plateau tops, ridgelines, and in the broader floodplain of major rivers over the region show similar slow lowering rates between 0.17 and 4.88 m.Myr ‐1, with a mean value of 1.0 ± 0.6 m.Myr ‐1 ( n =15), whilst two bedrock samples collected directly within river‐beds record rates that are one to two orders of magnitude higher (14.4 ± 1.5 and 20.9 ± 2.5 m.Myr ‐1, respectively). Bedrock 26 Al/ 10 Be ratios are all compatible with simple, continuous sub‐aerial exposure histories. Modern river sediment yield lower 10 Be and 26 Al concentrations, apparent 10 Be basin‐wide denudation rates ranging between 1.8 and 7.7 m.Myr ‐1, with a median value of 2.6 m.Myr ‐1, more than double the magnitude of bedrock erosion rates. 26 Al/ 10 Be ratios of the sediment samples are lower than those obtained for bedrock samples. We propose that these depleted 26 Al/ 10 Be ratios can largely be explained by the supply of sediment to river basins from the slab fragmentation and chemical weathering of channel gorge walls and plateau escarpments that result in diluting the cosmogenic nuclide concentration in river sediments measured at the basin outlets. The results of a mass‐balance model suggest that 60–90% of river sediment in the Kimberley results from the breakdown and chemical weathering of retreating vertical sandstone rock‐walls in contrast to sediment generated by bedrock weathering and erosion on the plateau tops. This study emphasises the value of analysing two or more isotopes in basin‐scale studies using cosmogenic nuclides, especially in slowly eroding post‐orogenic settings. © 2019 John Wiley & Sons, Ltd. Abstract : This study discusses the processes that control the cosmogenic nuclide concentration of river sediment in the Kimberley region of NW Australia where escarpment walls are prevalent. (A) If escarpment retreat is sufficiently slow and at steady state with respect to cosmogenic nuclide production, then a large proportion of the erosion surfaces will attain only 50% (green) of the nuclide concentration on the plateau top (red). (B) In addition to surface weathering at steady‐state, escarpment retreat can also progress by episodic spalling of blocks, allowing deep seated and fully shielded slabs to contribute sediment with highly depleted nuclide concentrations. Modelling results suggest that 60‐90% of river sediment in the Kimberley results from the breakdown and chemical weathering of retreating vertical rock‐walls in contrast to sediment generated by bedrock weathering and erosion on the plateau tops.